A new testate amoebae species Planhoogenraadia wuchanica sp. nov. from subtropical forest soils in Wuhan, central China - Bobrov, Anatoly; Qin, Yangmin; Payne, Richard J. (Zootaxa, 2019)
Here we describe a new testate amoeba species Planhoogenraadia wuchanica sp. nov. identified in subtropical forest soils in Wuhan, central China. The smaller shell length, narrower aperture and distinctive ‘cap’ structure make P. wuchanica morphologically distinct from similar taxa in the genus. While this new species is morphologically distinctive, phylogenetic analyses would be beneficial to clarify taxonomic relationships within the genus Planhoogenraadia.